Electrochemical performance of carbon-supported Pt(Cu) electrocatalysts for low-temperature fuel cells. (14th August 2020) - Garcia-Cardona, Julia; Sirés, Ignasi; Alcaide, Francisco; Brillas, Enric; Centellas, Francesc; Cabot, Pere L.
Abstract: Pt(Cu) nanoparticles supported on carbon nanofibers (CNFs), multi-walled carbon nanotubes (MWCNTs) and Vulcan carbon XC72, have been synthesized by electroless deposition and galvanic exchange. The structural analyses show contracted Pt fcc lattices due to the formation of a PtCu alloy core covered by a Pt-rich shell, mean crystallite sizes of about 3 nm, as well as good dispersion and carbon attachment. The electrochemical surface areas (ECSAs) of Pt(Cu)/CNF and Pt(Cu)/XC72 are comparable to those of commercial Pt/C and PtCu/C. The Pt(Cu) electrocatalysts show more negative onset potentials for CO oxidation than Pt/C and PtCu/C, thus indicating their greater CO tolerance. Pt(Cu)/CNF and Pt(Cu)/MWCNT present the highest mass activity and specific activity for the O2 reduction, respectively, both with better relative stability than Pt(Cu)/XC72. Pt(Cu)/CNF and Pt(Cu)/MWCNT are then considered good cathode catalysts, yielding estimated savings of about 50 wt% Pt, when applied to low-temperature fuel cells. Graphical abstract: Image 1 Highlights: The Pt(Cu) nanoparticles exhibited PtCu alloying with external Pt-rich shell. The supported Pt(Cu) catalysts had higher CO tolerance than commercial Pt/C and PtCu/C. The Pt(Cu) nanostructures of about 3 nm allowed saving the Pt amount by about 50 wt%. Pt(Cu)/CNF and Pt(Cu)/MWCNT had respectively the best mass and specific activity for ORR. Pt(Cu)/CNF and Pt(Cu)/MWCNT presented better relative stability than Pt(Cu)/XC72.